Vaccine Protection against Simian Immunodeficiency Virus by Recombinant Strains of Herpes Simplex Virus - Murphy, Cynthia G. (American Society for Microbiology, 2000)
An effective vaccine for AIDS may require development of novel vectors capable of eliciting long-lasting immune responses. Here we report the development and use of replication-competent and replication-defective strains of recombinant herpes simplex virus (HSV) that express envelope and Nef antigens of simian immunodeficiency virus (SIV). The HSV recombinants induced antienvelope antibody responses that persisted at relatively stable levels for months after the last administration. Two of seven rhesus monkeys vaccinated with recombinant HSV were solidly protected, and another showed a sustained reduction in viral load following rectal challenge with pathogenic SIVmac239 at 22 weeks following the last vaccine administration. HSV vectors thus show great promise for being able to elicit persistent immune responses and to provide durable protection against AIDS.